Analysis of Islamic Religious Education Learning Methods in Improving Student Learning Motivation in Malaysia - Juliana, Juliana; Setiawan, Hasrian Rudi (Ahlussunnah: Journal of Islamic Education, 2025)
The purpose of this study was to analyze Islamic Religious Education (PAI) materials taught at Tadika Bijak Lestari Penang, Malaysia, determine their effectiveness, and determine which variables support or hinder efforts to increase students' intrinsic learning desires. The research location was Tadika Bijak Lestari in Malaysia. Using in-depth interviews with the principal and class instructors as data sources, this qualitative technique employed a case study approach. Participants could be observed, interviews could be conducted, and notes could be kept as data collection techniques. According to this study, the learning strategies used were lectures, memorization, and basic interactive activities. However, research shows that student interest and engagement in learning are negatively impacted by the prevalence of lecture techniques. The availability of adequate educational facilities and certain student learning motivations are factors that facilitate the implementation of learning, but limited diversity of approaches and teachers' difficulties in adapting learning strategies are inhibiting factors. This study shows that Tadika Bijak Lestari Malaysia has successfully implemented various Islamic Religious Education (PAI) teaching strategies effectively. To achieve progress in this area, new approaches to Islamic Religious Education (PAI) that are more creative, flexible, and contextual are needed. By adapting creative techniques to the needs of early childhood, it is hoped that this will increase their enthusiasm for learning, which in turn will make the Islamic Religious Education learning process more relevant in building religious values ​​and holistic personality.